The Idealized Electoral College voting mechanism and shareholder power - Van Wesep, Edward D. (Journal of Financial Economics, 2014)
Increasing concern over corporate governance has led to calls for more shareholder influence over corporate decisions, but allowing shareholders to vote on more issues may not affect the quality of governance. We should expect instead that, under current rules, shareholder voting will implement the preferences of the majority of large shareholders and management. This is because majority rule offers little incentive for small shareholders to vote. I offer a potential remedy in the form of a new voting rule, the Idealized Electoral College (IEC), modeled on the American Electoral College, that significantly increases the expected impact that a given shareholder has on election. The benefit of the mechanism is that it induces greater turnout, but the cost is that it sometimes assigns a winner that is not preferred by a majority of voters. Therefore, for issues on which management and small shareholders are likely to disagree, the IEC is superior to majority rule.